Association between Percentage of Neutrophils at Admission and in-Hospital Events in Patients ≥75 Years of Age with Acute Coronary Syndrome - Cuihong Tian; Zhaowei Zhu; Hebin Xie; Cheng Wei; Zhenfei Fang; Xinqun Hu; Shenghua Zhou (Cardiovascular Innovations and Applications, 2023)
Objective: The study aimed to evaluate the role of the neutrophil percentage (N%) at admission in predicting in-hospital major adverse cardiovascular events (MACE) in patients ≥75 years of age with acute coronary syndrome (ACS). Methods: A total of 1189 patients above 75 years of age with ACS hospitalized at the Second Xiangya Hospital between January 2013 and December 2017 were enrolled in this retrospective study. Receiver operator characteristic curve analysis was performed to calculate the optimal N% cut-off value for patient grouping. The in-hospital MACE consisted of acute left heart failure, stroke and any cause of death. Multivariable logistic analyses were used to assess the role of N% in predicting MACE in older patients with ACS. Results: The patients were divided into a high N% group (N% ≥74.17%, n=396) and low N% group (N%<74.17%, n=793) according to the N% cut-off value (N%=74.17%). The rate of MACEs during hospitalization was considerably higher in the high N% group than the low N% group (27.5% vs. 9.6%, P<0.001). After adjustment for other factors, high N% remained an independent risk factor for in-hospital MACE in older patients with ACS (odds ratio 1.779, 95% confidence interval 1.091–2.901, P=0.021). Conclusion: High N% at admission is an independent risk factor for in-hospital MACE in patients above 75 years of age with ACS.